Revealing cooperative Li-ion migration in Li1+xAlxTi2−x(PO4)3 solid state electrolytes with high Al doping. Issue 1 (9th December 2019) - Zhang, Bingkai; Lin, Zhan; Dong, Huafeng; Wang, Lin-Wang; Pan, Feng
Abstract : The trapping effect of Al-dopants on Li-ions is greatly reduced at high Al-dopants due to the delocalization of polarization interactions and the depopulation of oxygen atoms, which results in a smooth energy landscape and destabilization of Li-ions. Abstract : Li1+ x Al x Ti2− x (PO4 )3 (LATP) is attracting attention as a promising inorganic solid electrolyte (ISE) with potential use in all-solid-state lithium-ion batteries. The objective of this paper is to examine and understand the effect of the Al-dopant concentration on the Li-ion diffusion of LATP using density functional theory and the molecular dynamics method. By comparing Li1.16 Al0.16 Ti1.84 (PO4 )3 (LATP-0.16) and Li1.33 Al0.33 Ti1.67 (PO4 )3 (LATP-0.33) with Li1.5 Al0.5 Ti1.5 (PO4 )3 (LATP-0.50), LATP-0.50 is expected to have higher ionic conductivity. The trapping effect of Al-dopants on Li-ions is greatly reduced in LATP-0.50 due to the delocalization of polarization interactions and the depopulation of oxygen atoms, which results in a smooth energy landscape and destabilization of Li-ions. The energy difference of adjacent Li-ions and binding interaction of Li–Li due to a specific local configuration of two Li-ions alternately enable cooperative migration of Li-ions. This understanding of high Li-ion diffusion is important in interpreting the experimental results aiming to assess the effects of Al-dopants on Li-ion conductivity and can be used by researchers to engineer these materials for batteries.